Pigeons - Tiziano Toracca (Law Text Culture, 2018)
I guess it was a couple of instants after knowing that an airliner crashed into one of the towers of the World Trade Center, the North Tower, right after having received a phone call from a colleague based in Boston, area code 617. He had been awake for two hours already. He had thanked Caroline, hung up the phone, turned the radio on and he had started to get changed – thinking that it was absurd to envy those who were sitting on the boat and were passing in front of the Irish Hunger Memorial for 36 Dollars. It had been one of them: one of those had called Caroline to tell her what was going on. He said so: his name was Colin something. But how on earth could he have told her that he was excited about what was going on? After the phone call with Caroline Bloom, Michael Taro Yamasaky had received other calls, even Matthew O’Brian had called, a prison warden at Jackson State Prison, one with the balls, they would say, one who was not afraid to fill in surveillance reports in prison cells, alone, just with paper and pen.